ANALISIS PENGARUH CITRA MEREK, PERSEPSI HARGA, KUALITAS PRODUK, DAN PROGRAM PROMOSI TERHADAP LOYALITAS PELANGGAN (Survei pada Pelanggan Madu Arbain di Surakarta) - Sukarna, Sukarna; Suddin, Alwi; Sutarno, Sutarno (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
This study aims to analyze the influence of brand image, product quality, price perception and promotion program of the loyalty of arbain honey customers in Surakarta. The population of this research is all arbain honey customers in all sub-districts in Surakarta city by using a sample of 100 respondents, which are limited to customers only by purposive sampling method. Data collection techniques using questionnaire instruments through testing validity and reliability. Processing data using spss version 21. Regression requirements test using classical assumption test while hypothesis testing using multiple linear regression test, t test, F test and coefficient of determination (R2). The test results using the t test can be concluded that brand image, product quality, and promotion program partially have a significant effect on the loyalty of arbain honey customers in Surakarta, with the three of p-value < 0.05. But based on the results of the t test also states that the perception of prices does not significantly influence the loyalty of arbain honey customers in Surakarta with a p-value of 0.309 > 0.05. The test results also show that the brand image has the most dominant influence on customer loyalty of arbain honey products in Surakarta with a regression coefficient of 0.320.